Mask-based immobilization in Gamma Knife stereotactic radiosurgery. (January 2021) - Bush, Aaron; Vallow, Laura; Ruiz-Garcia, Henry; Herchko, Steven; Reimer, Ronald; Ko, Stephen; May, Byron; Trifiletti, Daniel M.; Peterson, Jennifer
Highlights: The Gamma Knife Icon is the first cobalt-based SRS unit to support a mask vs a frame. We retrospectively reviewed 124 patients treated with Gamma Knife SRS using a mask. 24 patients presented with primary brain tumors and 100 patients with metastases. Median doses to metastases were 20 Gy in 1 and 25 Gy in 5 fractions. Response rates are encouraging, and continued follow-up will be necessary. Abstract: The Gamma Knife Icon (Elekta AB, Stockholm) is a cobalt-based stereotactic radiosurgery (SRS) unit to support the use of a thermoplastic mask in lieu of a rigid frame, using an onboard cone-beam CT (CBCT) and an intrafraction motion management system (IFMM). We retrospectively reviewed 124 patients treated with Gamma Knife SRS from January 2018 to December 2019 at our institution using a mask-based immobilization system. Patient and treatment characteristics were collected and summarized as well as interfraction shifts and treatment-related outcomes. This dataset includes 124 patients with an associated 358 intracranial tumors. Twenty-four patients presented with primary brain tumors, which included 14 meningiomas and 10 other histologies, with 100 patients having brain metastases. Sixty tumors were post-operative, while 298 were intact. The median dose for primary tumors was 25 Gy in 5 fractions. Median doses to metastases were 20 Gy in 1 fraction, 27 Gy in 3 fractions, and 25 Gy in 5 fractions. Median interfraction CBCT shifts were submillimeter. Median patient follow-up was 6.28 months. 91% of patients with metastases maintained local control. Our early clinical experience has demonstrated limited toxicity profiles and high patient tolerance, which suggests that mask-based Gamma Knife SRS provides a safe alternative option for frameless SRS. Patients with large target volumes where fractionation is preferred or with small target volumes in non-eloquent areas can be considered for this approach. Response rates are encouraging, and continued follow-up is necessary to investigate long-term control and survival.